2009
DOI: 10.1007/s13199-009-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution of reproductive characteristics in three dioecious fig species and their pollinator wasps

Abstract: This study investigates dioecious fig species using a pollinator introduction experiment. Our aims were to determine: (1) whether there was a significant difference in foundress distribution between sexes per fig species; (2) whether fig size and foundress number affect reproductive success of dioecious figs; and (3) who is the 'controlling partner' in the fig/pollinator mutualism. Three dioecious fig species: Ficus semicordata, Ficus hispida and Ficus tinctoria from Xishuangbanna, China, were selected for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The specialized nature of fig/pollinator interactions has made the system a focal point for studies of coevolution (Herre 1989;Ganeshaiah et al 1995;Weiblen 2004;Ma et al 2009). Each Ficus species is associated with one or several pollinating fig wasp species (Herre et al 2008) and approximately parallel patterns of phylogenetic diversity among more than 800 taxa has drawn much speculation on processes of diversification (Weiblen and Bush 2002;Machado et al 2005;Jackson et al 2008;Jousselin et al 2008).…”
Section: Ficus Versus Castilleaementioning
confidence: 99%
“…The specialized nature of fig/pollinator interactions has made the system a focal point for studies of coevolution (Herre 1989;Ganeshaiah et al 1995;Weiblen 2004;Ma et al 2009). Each Ficus species is associated with one or several pollinating fig wasp species (Herre et al 2008) and approximately parallel patterns of phylogenetic diversity among more than 800 taxa has drawn much speculation on processes of diversification (Weiblen and Bush 2002;Machado et al 2005;Jackson et al 2008;Jousselin et al 2008).…”
Section: Ficus Versus Castilleaementioning
confidence: 99%
“…In support of this assertion, Bronstein (1988) found that seed set in F. pertusa L. is pollinator-limited and Harrison et al (2000) suggested for dioecious figs that fig abortion of female trees is likely to reflect pollen limitation. Ma et al (2009) also showed that the numbers and the proportions of fig seeds and female wasp offspring significantly increased with numbers of foundresses.…”
Section: General Leaf and Fig Phenologymentioning
confidence: 87%
“…It is noteworthy that the natural foundress distributions of F. hispida show that receptive figs predominately contain either one or two foundresses (Patel and Hossaert‐McKey , Ma et al. ; Y. Q. Peng, unpublished data ). The likely low frequency of natural P− wasps (sensu Jandér and Herre ), would thus result in a very low probability that any single fig would contain multiple P− foundresses.…”
Section: Discussionmentioning
confidence: 99%